2018
DOI: 10.1155/2018/7628957
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Maternal Plasma and Cord Blood Levels in Mothers with Spontaneous Preterm and Term Delivery

Abstract: Irisin, an adipomyokine identified in 2012, has been investigated in association with common pregnancy complications, including gestational diabetes mellitus, preeclampsia, and intrauterine growth restriction. The objective of this study is to examine the potential role of irisin in preterm birth (PTB) by comparing its level between mothers with term and preterm labor. Maternal peripheral blood and cord blood samples were collected from 30 mothers who delivered prematurely and from 35 mothers who delivered at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…In that study, irisin concentrations were reported in the range of 3-5 ng/ml [42] which is lower than the values reported herein. However, our findings are of a similar magnitude with other published studies using the same ELISA kit [43][44][45][46] and indeed slightly higher than the Tandem Mass Spectrometry but significantly lower compared to assays used in different studies. In fact, our assay's linear range is 1.29-27.5 ng/ml, and the assay can detect irisin levels between 10 and 50 ng/ml.…”
Section: Discussionsupporting
confidence: 90%
“…In that study, irisin concentrations were reported in the range of 3-5 ng/ml [42] which is lower than the values reported herein. However, our findings are of a similar magnitude with other published studies using the same ELISA kit [43][44][45][46] and indeed slightly higher than the Tandem Mass Spectrometry but significantly lower compared to assays used in different studies. In fact, our assay's linear range is 1.29-27.5 ng/ml, and the assay can detect irisin levels between 10 and 50 ng/ml.…”
Section: Discussionsupporting
confidence: 90%
“…A higher irisin level in preterm infants compared with term deliveries was discovered. It could be described by the fact that the onset of labor provides a strong stimulus for the release of irisin into maternal and fetal circulations [ 145 , 151 ], and could increase cord blood irisin level by nearly 40% [ 152 ]. In addition, it has been suggested that increased irisin release into cord blood may be caused by temporary uteroplacental ischemia during vaginal delivery, thus leading to fetal stress [ 145 ].…”
Section: Clinical Applications Of Adipokines Measurements In Variomentioning
confidence: 99%
“…Measurement of irisin in umbilical cord blood has shown that irisin levels are lower in small for gestational age (SGA) newborns compared with appropriate for gestational age (AGA) and large for gestational age (LGA) neonates [36,37,38]. In contrast, in a study of Caucasian women, a higher irisin level in preterm infants compared with term infants was found [39]. Irisin levels were also significantly higher in maternal blood compared with umbilical cord blood.…”
Section: Association Of Circulating Irisin With Mother–offspring Rmentioning
confidence: 99%